Trilliumosides K and L, two novel steroidal saponins from rhizomes of Trillium govanianum, as potent anti-cancer agents targeting apoptosis in the A-549 cancer cell line - Lone, Bashir Ahmad; Tabassum, Misbah; Bhushan, Anil; Rani, Dixhya; Dhiman, Urvashi; Ahmad, Ajaz; Mir, Hilal Ahmad; Gupta, Prem N.; Mondhe, D. M.; Gairola, Sumeet; Gupta, Prasoon (Frontiers in Chemistry, 2023)
Two novel steroidal saponins, trilliumosides A (1) and B (2), were isolated from the rhizomes of Trillium govanianum led by bioactivity-guided phytochemical investigation along with seven known compounds govanoside D (3) protodioscin (4), borassoside E (5), 20-hydroxyecdysone (6), 5,20-hydroxyecdysone (7), govanic acid (8) and diosgenin (9). The structure of novel compounds 1-2 were established using analysis of spectroscopic data including 1D, 2D nuclear magnetic resonance (NMR) and high resolution mass spectrometry (HR-ESI-MS) data. All isolated compounds were evaluated for in-vitro cytotoxic activity against a panel of human cancer cell lines. Compound (1) showed significant cytotoxic activity against A-549 (Lung) and SW-620 (Colon) cancer cell lines with IC50 values of 1.83 & 1.85 µM, whereas Compound (2) IC50 value against A-549 cell line was found to be 1.79 µM respectively. Among previously known compounds (3), ( 5) and ( 9) their cytotoxic IC50 value was found to be in the range of 5-10 µM. Comprehensive anti-cancer investigation revealed that Compound (2) inhibited in-vitro migration and colony forming capability in the A-549 cell line. Additionally, the mechanistic analysis of Compound (2) on the A-549 cell line indicated distinctive alterations in nuclear morphology, increased reactive oxygen species (ROS) production, and decreased levels of mitochondrial membrane potential (MMP). By upregulating the pro-apoptotic protein BAX and downregulating the anti-apoptotic protein BCL-2, the aforementioned actions eventually cause apoptosis, a crucial hallmark in cancer research, which activates Caspase-3. To the best of our knowledge, this study reports the first mechanistic anti-cancer evaluation of the compounds isolated from the rhizomes of Trillium govanianum with remarkable cytotoxic activity in the desired micromolar range.